COMMUNICATION PATTERN OF PC IPPNU PONOROGO ORGANIZATION IN OVERCOMING INTERNAL CONFLICTS - Zayinnatul Ula, Azza Fahreza; Hanifah, Irma Rumtiating Uswatun (QAULAN: Journal of Islamic Communication, 2023)
In organizations, maintaining harmonious relationships is essential in managing material, financial, and human resources. Overcoming internal conflicts is one of the challenges in managing and leading members. Conflicts that are not resolved immediately will hinder the organization in achieving goals. Therefore, there is a need for appropriate and effective communication patterns for conflict resolution. This study aims to determine how the pattern of organizational communication carried out by PC IPPNU Ponorogo Regency in overcoming internal conflicts. The method used is a qualitative approach to field research with descriptive methods. The data collection techniques used were participant observation, interviews, and documentation. The study results were obtained: 1) There are 4 forms of internal conflict, including conflicts within individuals, conflicts between individuals, conflicts between members in one group, and intra-organizational conflicts caused by communication factors, organizational structure factors, and personal factors. 2) Communication patterns in overcoming internal conflicts, namely the star model through horizontal and informal communication and the chain model through formal communication networks, including upward and downward communication. Both emphasize the existence of common interests and common goals that can foster each member's proactive nature and mutual openness to actively participate in resolving internal organizational conflicts.